Mathematical Progress in Expressive Image Synthesis II Extended and Selected Results from the Symposium MEIS2014 - Ochiai, Hiroyuki; Anjyo, Ken (Mathematics for Industry,, 2015)
The material included in this book provides selected presentations given at the international symposium MEIS2014. The book aims to provide a unique venue where various issues in computer graphics (CG) application fields are discussed by mathematicians as well as CG researchers and practitioners. The target audience is not limited to researchers in academia but also those in industries with a strong interest in digital media creation, scientific visualization, and visual engineering. .